Teacher Self-Efficacy and Perceived Autonomy: Relations with Teacher Engagement, Job Satisfaction, and Emotional Exhaustion. Issue 1 (February 2014) - Skaalvik, Einar M.; Skaalvik, Sidsel
When studied separately, research shows that both teacher self-efficacy and teacher autonomy are associated with adaptive motivational and emotional outcomes. This study tested whether teacher self-efficacy and teacher autonomy are independently associated with engagement, job satisfaction, and emotional exhaustion. 2, 569 Norwegian teachers in elementary school and middle school (719 men, 1, 850 women; M age=45.0 yr., SD =11.5) were administered the Norwegian Teacher Self-Efficacy Scale, the Teacher Autonomy Scale, the Utrecht Work Engagement Scale, the Teacher Job Satisfaction Scale, and the Maslach Burnout Inventory. The analysis revealed that both teacher autonomy and self-efficacy were independent predictors of engagement, job satisfaction, and emotional exhaustion. This study suggests that autonomy or decision latitude works positively but through different processes for teachers with high and low mastery expectations.